Testing mediating effect of customer gratitude on Islamic relationship marketing practice in Malaysian takaful industry - Che Mohd Salleh, Marhanum (2015)
Parallel to the achievement of the Takaful industry, agency system becomes the main medium utilised by the industry to educate the public and assist them about future financial preparation. As a mirror to an Islamic type of insurance, Takaful agents play significant role not limited to sell the Takaful products, but to behave base on the Islamic norms in front of their customers. Thus, this research introduces the features of Islamic relationship marketing and investigates its significance towards customer gratitude, trust, and commitment in the industry. A total of 741 of Family Takaful customers located in Klang Valley participated in this study. Based on analysis, Islamic relationship marketing (IRM) have significantly affected customer gratitude, trust, and commitment. Customer gratitude is found to partially mediate the relationship of IRM-customer trust and IRM-customer commitment via PLS analysis. These results are important to the industry to enhance its marketing approach for future customer retention.